2017
DOI: 10.1149/07711.0413ecst
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Sulfur Battery with a New Magnesium Powder Anode

Abstract: Herein we report a magnesium powder anode with medium capacity retention and recovery of potential plateaus over reversible cycling. Furthermore powder anodes showed an optimized behavior during charging leading to an improved coulomb efficiency compared to magnesium foil anodes. Battery cells with a powder anode showed pronounced voltage plateaus and no problem to reach a 2.8 V cutoff voltage. Within the compaction pressure range investigated a magnesium powder anode prepared by relatively low pressures showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 15 publications
0
41
0
Order By: Relevance
“…Clearly, cells containing a pressed anode (Figure a,b) showed better Coulombic efficiencies than those based on a Mg foil (Figure c) due to a more efficient charging . Furthermore, cells containing pressed anodes lasted for 100 cycles while those based on Mg foil were reported to fail after only 15 cycles . Notably, the authors also found that cells containing pressed anodes prepared at low pressure showed better electrochemical behavior and better voltage plateau recovery than those based on PAHP .…”
Section: Anode Materialsmentioning
confidence: 95%
See 4 more Smart Citations
“…Clearly, cells containing a pressed anode (Figure a,b) showed better Coulombic efficiencies than those based on a Mg foil (Figure c) due to a more efficient charging . Furthermore, cells containing pressed anodes lasted for 100 cycles while those based on Mg foil were reported to fail after only 15 cycles . Notably, the authors also found that cells containing pressed anodes prepared at low pressure showed better electrochemical behavior and better voltage plateau recovery than those based on PAHP .…”
Section: Anode Materialsmentioning
confidence: 95%
“…Clearly, cells containing a pressed anode (Figure a,b) showed better Coulombic efficiencies than those based on a Mg foil (Figure c) due to a more efficient charging . Furthermore, cells containing pressed anodes lasted for 100 cycles while those based on Mg foil were reported to fail after only 15 cycles .…”
Section: Anode Materialsmentioning
confidence: 95%
See 3 more Smart Citations